Sintomas depressivos em indivíduos que frequentam grupoterapia contra o tabagismo - Santos, Camila Barbosa dos (2017)
Tobacco dependence is one of the major public health problems and one that most damages people's health. Evaluating strategies that help combat smoking and strengthening emotional resources, is an essential condition for the referral to effective interventions, which aid in the recovery of patients. This study aims to evaluate the effects of cognitive behavioral th erapy group, associated with drug treatments, in the fight against smoking and in the strengthening of ego resources. Participating in this study were 60 adults, aged 18 years and over, regardless of gender, marital status, schooling and socioeconomic levels, and profession, from a Psychosocial Care Center for Alcohol and Other Drugs (CAPS AD) located in Cruz Alta, Region of the State of Rio Grande do Sul. Participants in the study responded individually to the following instruments: Sociodemographic Questi onnaire, Fagerstrom Test, Beck Depression Scale (BDIII), Depressive Thinking Scale (EPD). The cognitive behavioral therapy group was performed weekly, with an approximate duration of 1 hour and 15 min each session, in the CAPS-AD, with the GI. The presentation of the numerical variables can be described as mean ± standard deviation or median (p25-p75), and its distribution is normal or not. Among the contributions, the study may assist in directing more effective interventions against the smoking of users of the Center for Psychosocial Care Alcohol and other Drugs, reassuring the importance of cognitive behavioral therapy group, associated with drug treatments, in the fight against smoking and strengthening Of ego resources as a method of evaluation in this context.